EFEKTIVITAS CELEBRITY ENDORSEMENT DALAM MENINGKATKAN BRAND AWARENESS DAN MINAT BELI KONSUMEN: KAJIAN LITERATUR - Agustina Tri Wuryani; Sarah Rahmawati; Muh Fikri Ananda Putra; Pupung Purnamasari (Cahaya Ilmu Bangsa, 2024)
This research aims to examine the impact of celebrity endorsement in increasing brand awareness and consumer purchase intention. Using the academic literature review method with a focus on previous studies on the relationship between celebrity endorsement in optimizing brand awareness. The results show that celebrity endorsement contributes significantly to building brand awareness and increasing consumer purchase intention where, celebrities who have high credibility, attractiveness, and relevance to the target audience are able to increase brand visibility and significantly influence consumer purchasing decisions. Through this study, it is hoped that companies can understand how to optimally utilize celebrity endorsements to create effective and efficient marketing strategies.